Drug-Drug Interactions of Glecaprevir and Pibrentasvir Coadministered With Human Immunodeficiency Virus Antiretrovirals. (29th August 2019) - Kosloski, Matthew P; Oberoi, Rajneet; Wang, Stanley; Viani, Rolando M; Asatryan, Armen; Hu, Beibei; Ding, Bifeng; Qi, Xin; Kim, Elaine J; Mensa, Federico; Kort, Jens; Liu, Wei
Abstract: Background: Treatment of patients coinfected with hepatitis C and human immunodeficiency viruses (HCV; HIV) requires careful consideration of potential drug-drug interactions between HCV direct-acting antiviral agents (DAA) and HIV antiretrovirals. Glecaprevir/pibrentasvir is a fixed-dose combination of an NS3/4A protease inhibitor and an NS5A inhibitor approved for the treatment of chronic HCV genotype 1–6 infection, including patients with HIV coinfection. Methods: A series of phase 1 studies was conducted to evaluate potential interactions of glecaprevir and pibrentasvir with elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide, abacavir/dolutegravir/lamivudine, raltegravir, rilpivirine, atazanavir/ritonavir, darunavir/ritonavir, lopinavir/ritonavir, or efavirenz/emtricitabine/tenofovir disoproxil fumarate. Pharmacokinetics of the antiretrovirals and DAAs were characterized when administered alone and in combination to quantify changes in systemic drug exposure. Results: Glecaprevir area under the curve increased >4-fold in the presence of ritonavir-boosted HIV protease inhibitors, while pibrentasvir concentrations were not significantly affected; elevations in alanine transaminase occurred in combination with atazanavir/ritonavir only. Exposures of glecaprevir and pibrentasvir may be significantly decreased by efavirenz. Coadministration with glecaprevir and pibrentasvir did not result in clinically significant changes in the exposure of any antiretroviral agents. Conclusions: Atazanavir is contraindicated with glecaprevir/pibrentasvir and use of boosted protease inhibitors or efavirenz is not recommended. No clinically significant interactions were observed with other studied antiretrovirals. Abstract : Concurrent treatment of chronic HCV infection with direct-acting antiviral agents and HIV infection with antiretroviral agents in coinfected patients requires careful consideration of potential drug-drug interactions. Results and implications of clinical studies for glecaprevir/pibrentasvir with 15 antiretroviral agents are summarized.